2021
DOI: 10.1016/j.lanwpc.2021.100094
|View full text |Cite
|
Sign up to set email alerts
|

Antibody seroprevalence in the epicenter Wuhan, Hubei, and six selected provinces after containment of the first epidemic wave of COVID-19 in China

Abstract: Background China implemented containment measures to stop SARS-CoV-2 transmission in response to the COVID-19 epidemic. After the first epidemic wave, we conducted population-based serological surveys to determine extent of infection, risk factors for infection, and neutralization antibody levels to assess the real infections in the random sampled population. Methods We used a multistage, stratified cluster random sampling strategy to conduct serological surveys in thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…Therefore, relying on hospitalization or testing rates alone underestimates the true disease burden [ 6 , 7 ]. Li et al found that the SARS-CoV-2 infection rate of children at the early stage of the epidemic in Wuhan was 2.4%–3.1%, with the overall infection rate of 4.4% [ 8 ]. Subsequent studies have shown consistently that children and adolescents are as likely to be infected as the adult population [ 9 – 11 ].…”
Section: Epidemiological Burden Of Covid-19 In Childrenmentioning
confidence: 99%
“…Therefore, relying on hospitalization or testing rates alone underestimates the true disease burden [ 6 , 7 ]. Li et al found that the SARS-CoV-2 infection rate of children at the early stage of the epidemic in Wuhan was 2.4%–3.1%, with the overall infection rate of 4.4% [ 8 ]. Subsequent studies have shown consistently that children and adolescents are as likely to be infected as the adult population [ 9 – 11 ].…”
Section: Epidemiological Burden Of Covid-19 In Childrenmentioning
confidence: 99%
“…The secondary goal is to protect the high-risk population, which is more vulnerable to severe clinical illness once infected, including people with underlying conditions and older adults 60 years of age or above [11,13]. Considering variations in the risk of severe outcomes given SARS-CoV-2 infection across age groups [14,15], we further categorized the target population into (1) individuals aged 60 or over at least one underlying condition; (2) The tertiary goal is to contain SARS-CoV-2 transmission, and thus the target population includes other individuals under 60 years of age without underlying conditions, i.e., working-age people (18-59 years), school-aged children (6-17 years) and younger children (0-5 years) [11,13]. The detailed definition of priority groups is presented in Additional file 1: Table S1.…”
Section: Definition Of the Priority Target Population For The Covid-19 Vaccination Programmentioning
confidence: 99%
“…Author details 1 Shanghai Institute of Infectious Disease and Biosecurity, School of Public Health, Fudan University, Shanghai, China. 2 Key Laboratory of Public Health Safety, Ministry of Education, Fudan University, Shanghai, China. 3 Department of Infectious Diseases, Huashan Hospital, Fudan University, Shanghai, China.…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…antibody positivity in parts of the world that had more cases early on in the pandemic, including other parts of the United States (3.2-6.9%) [9], Wuhan, China (4.4%) [15], Spain (4.6%) [16], Geneva (4.8%) [17], Ariano Irpino, Italy (5.6%) [18], and northern Iran (22.2%) [19].…”
Section: Plos Onementioning
confidence: 99%